2012
DOI: 10.1080/02786826.2012.693977
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Charged Nanoparticles During the Synthesis of GaN Nanostructures by Atmospheric-Pressure Chemical Vapor Deposition

Abstract: The possibility that GaN charged nanoparticles might be generated during the synthesis of GaN nanostructures was examined in an atmospheric-pressure chemical vapor deposition (CVD) process using a differential mobility analyzer combined with a Faraday cup electrometer. Both positively and negatively charged nanoparticles in the size range of 10-100 nm were generated in the reactor of the CVD process using Ga 2 O 3 precursor and NH 3 gas. With decreasing flow rate of NH 3 from 400 to 0 standard cubic centimeter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…In relation to this question, we observed consistently that nanowires tend to grow when nanoparticles are relatively small and their number density is also relatively small. 25,27 One possibility to explain this observation would be that the probability of CNPs to land on nanowires in the radial direction increases with increasing number density of nanoparticles, so the tendency for exclusive attachment of CNPs at the tips of nanowires would decrease. It should be noted that the radial direction to the tips of the nanowires has an advantage over the axial direction to the tips in that the former provides a larger area for attachment of CNPs than the latter.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to this question, we observed consistently that nanowires tend to grow when nanoparticles are relatively small and their number density is also relatively small. 25,27 One possibility to explain this observation would be that the probability of CNPs to land on nanowires in the radial direction increases with increasing number density of nanoparticles, so the tendency for exclusive attachment of CNPs at the tips of nanowires would decrease. It should be noted that the radial direction to the tips of the nanowires has an advantage over the axial direction to the tips in that the former provides a larger area for attachment of CNPs than the latter.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The amount of CNPs, which were size-classified by DMA, was measured as a current on the FCE. Our measurement system did not use the charging system because nanoparticles are self-charged in the quartz reactor of the CVD system ,, The number concentration and size distribution of the CNPs were measured during the syntheses of silicon nanowires and films, respectively, at N 2 gas flow rates of 500 and 1000 sccm. Electrically neutral nanoparticles were expected to exist in the CVD reactor; however, their fraction was unknown in the present experiment.…”
Section: Experimental Proceduresmentioning
confidence: 99%
“…For measurements by the DMA, the substrate holder and the grounded plate were taken out of the reactor, and a small quartz tube with an inner diameter of 4 mm was placed in the outlet of the reactor at a distance of 11 cm away from the source materials (800 °C) and was connected to the DMA-FCE system at the outside of the reactor. The DMA-FCE system could not only confirm the generation of charged particles in the gas phase but also measure their size distribution. ,, , Normally, particles are electrically charged by artificial charging for measurements by the DMA. However, we did not use an artificial charger because ZnO nanoparticles were self-charged in the reactor.…”
Section: Methodsmentioning
confidence: 99%
“…The abundant generation of charged nanoparticles was confirmed during the syntheses of diamond films, 3,4 zirconia films, 5 copper films, 6 silicon films, 7,8 silicon nanowires, 9 ZnO nanowires, 10 carbon nanotubes, 11,12 and GaN films or nanowires. 13 Considering these results, the generation of charged nanoparticles is so general that it appears to be the rule rather than the exception in the CVD process.…”
Section: Introductionmentioning
confidence: 98%
“…In the chemical vapor deposition (CVD) process, it has been believed that the reactant gases decompose mainly on the surface and produce atoms or molecules, which contribute to the growth of films or nanostructures . However, recently it has been shown that the reactant gases also decompose actively in the gas phase in many CVD systems, which is evidenced by the extensive generation of the gas phase nuclei. Using a differential mobility analyzer (DMA) or other particle detecting systems attached to a CVD reactor, Adachi et al , made an extensive study that a huge amount of SiO 2 nanoparticles was generated in the gas phase almost unavoidably under the deposition condition of SiO 2 films. The abundant generation of charged nanoparticles was confirmed during the syntheses of diamond films, , zirconia films, copper films, silicon films, , silicon nanowires, ZnO nanowires, carbon nanotubes, , and GaN films or nanowires .…”
Section: Introductionmentioning
confidence: 99%